Gastroesophageal reflux disease and vocal disturbances - Henry,Maria Aparecida Coelho de Arruda (2011)
CONTEXT: Gastroesophageal reflux disease is a chronic disease in which gastroduodenal contents reflux into the esophagus. The clinical picture of gastroesophageal reflux disease is usually composed by heartburn and regurgitation (typical manifestations). Atypical manifestations (vocal disturbances and asthma) may also be complaint. OBJECTIVE: To analyse the clinical, endoscopic, manometric and pHmetric aspects of patients suffering from gastroesophageal reflux disease associated with vocal disturbances. METHODS: Fifty patients with gastroesophageal reflux disease were studied, including 25 with vocal disturbances (group 1 - G1) and 25 without these symptoms (group 2 - G2). All patients were submitted to endoscopy, manometry and esophageal pHmetry (2 probes). The group 1 patients were submitted to videolaryngoscopy. RESULTS: Endoscopic findings: non-erosive reflux disease was observed in 95% of G1 patients and 88% of G2. Videolaryngoscopy: vocal fold congestion, asymmetry, nodules and polyps were observed in G1 patients. Manometric findings: pressure in the lower esophageal sphincter (mm Hg): 11.6 ± 5.2 in G1 and 14.0 ± 6.2 in G2 (P = 0.14); pressure in the upper esophageal sphincter (mm Hg): 58.4 ± 15.9 in G1 and 69.5 ± 30.7 in the controls. pHmetric findings: De Meester index: 34.0 ± 20.9 in G1 and 15.4 ± 9.4 in G2 (P<0.001); number of reflux episodes in distal probe: 43.0 ± 20.4 in G1 and 26.4 ± 17.2 in G2 (P = 0.003); percentage of time with esophageal pH value lower than 4 units (distal sensor): 9.0% ± 6.4% in G1 and 3.4% ± 2.1% in G2 (P<0.001); number of reflux episodes in proximal probe: 7.5 ± 10.9 in G1 and 5.3 ± 5.7 in G2 (P = 0.38); percentage of time with esophageal pH values lower than 4 units (Proximal probe): 1.2 ± 2.7 in G1 and 0.5 ± 0.7 in G2 (P = 0.21). CONCLUSIONS: 1) The clinical, endoscopic, and manometric findings observed in patients with vocal disturbance do not differ from those without these symptoms; 2) gastroesophageal reflux intensity is higher in patients with vocal disturbance; 3) patients without vocal disturbance can also present reflux episodes in the proximal probe.